«Il manque un anneau a la chaine»: The Brave Experiment of the ‘Scientific Property’ (Italian Review of Legal History, 2015)
Between the Twenties and Thirties of the Twentieth Century, the theme of ‘scientific property’ reaches its peak of interest among the European legal science. It is the most visible part of a short path winding between the last two decades of the Nineteenth Century and the first decade of the twentieth century, a path full of intersections with crucial issues of contemporary legal history. The main characters of this story are the new forms of intellectual activity that contribute in a sensational way to delineate the physiognomy of modernity, marked by the increasingly impetuous trait of the scientific and technological development. From the first attentions addressed to the rights of savants on their œuvres ou découvertes scientifiques (with the project of an international convention drafted by Francesco Ruffini for the League of Nations) until the dissolution of the interest in this issue, mainly juxtapositions – between social and economic forces, but also among the different conceptions of ‘law’ – and theoretical contrasts, as well as political ones, stand out inside national and European scientific discourse. This is a conflict that, on the one hand, has inevitably precluded the ‘scientific property’ the outlet to the ius positum, while on the other hand, it has made it a sort of valuable experimental laboratory for the jurist.
Keywords: Scientific property; contemporary legal history; intellectual property; League of Nations; Italian legal science